Living qur'an: Al-qur'an reception in al muhammad cepu islamic boarding school - Hakki Akmal Labib; M. Imam Pamungkas (Yayasan Azhar Amanaa Yogyakarta, 2024)
This research aims to analyze the reception of the Qur'an at the Al Muhammad Islamic Boarding School in Cepu. This is a qualitative research using inductive descriptive methods. Qualitative research is a research procedure that analyzes descriptive data in the form of spoken or written observations. The inductive descriptive method aims to describe and analyze data to obtain a general overview or description of the reception of the Qur'an at the Al Muhammad Islamic Boarding School. This research asserts that the Qur'an is a holy book that is always in harmony with all situations and conditions (ṣāliḥ li kulli zamān wa makān). The theory used by the researcher here is Karl Mannheim's sociology of meaning theory, which emphasizes three typologies of meaning, namely objective, expressive, and documentary meanings. This research yields at least two findings. First, various types of reception are found at the Al Muhammad Islamic Boarding School. Second, the meanings attached to these receptions include: a) objective meaning, where the various reception behaviors at the Al Muhammad Islamic Boarding School are part of a symbol of compliance and reverence for the boarding school's rules, b) expressive meaning is manifested in the form of self-internalization with positive values in the continuous learning process of the Qur'an, and c) documentary meaning is manifested in the form of local contextualization of the overall cultural system.